2016
DOI: 10.3390/ijms17081271
|View full text |Cite
|
Sign up to set email alerts
|

The FKBP5 Gene Affects Alcohol Drinking in Knockout Mice and Is Implicated in Alcohol Drinking in Humans

Abstract: FKBP5 encodes FK506-binding protein 5, a glucocorticoid receptor (GR)-binding protein implicated in various psychiatric disorders and alcohol withdrawal severity. The purpose of this study is to characterize alcohol preference and related phenotypes in Fkbp5 knockout (KO) mice and to examine the role of FKBP5 in human alcohol consumption. The following experiments were performed to characterize Fkpb5 KO mice. (1) Fkbp5 KO and wild-type (WT) EtOH consumption was tested using a two-bottle choice paradigm; (2) Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…The present study identified 129 genes (FDR < 0.05) that were differentially expressed in alcohol dependent subjects (Supplementary table 1). FKBP5, a well studied gene that is asoociated with alcohol use [28][29][30][31] , showed increased expression in the PFC of alcohol dependent subjects in our differential gene expression analysis (l 2 FC 0.27; P = 4.57 x 10 -7 ). Other studies have also shown that FKBP5 plays a role in alcohol drinking behaviors in rodents 28,29 and humans 32 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The present study identified 129 genes (FDR < 0.05) that were differentially expressed in alcohol dependent subjects (Supplementary table 1). FKBP5, a well studied gene that is asoociated with alcohol use [28][29][30][31] , showed increased expression in the PFC of alcohol dependent subjects in our differential gene expression analysis (l 2 FC 0.27; P = 4.57 x 10 -7 ). Other studies have also shown that FKBP5 plays a role in alcohol drinking behaviors in rodents 28,29 and humans 32 .…”
Section: Discussionmentioning
confidence: 70%
“…Other studies have also shown that FKBP5 plays a role in alcohol drinking behaviors in rodents 28,29 and humans 32 . FKBP5 encodes FK506-binding protein 5, a glucocorticoid receptor (GR)-binding protein implicated in various psychiatric disorders and alcohol withdrawal severity 30 . Qiu and colleagues 30 reported that Fkbp5 KO mice exhibited increased alcohol consumption compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study investigating the association between polymorphisms in NR3C1 and suicide attempts in 597 affective disorder patients reports no difference between groups with and without a history of suicide attempts (71). Recent studies show SNPs in FKBP5 and NR3C1 to be associated with alcohol drinking and crucial for alcohol abuse interventions (72, 73). …”
Section: Genetic Risk Constellationmentioning
confidence: 99%
“…Among these, the strongest interaction effect was observed for FKBP5 and rs9394312. Several studies have implicated FKBP5 in the severity of alcohol withdrawal (72), alcohol drinking patterns in rodents (73), problematic drinking (74), as well as direct regulation of FKBP5 expression and phosphorylation by acute ethanol in mouse prefrontal cortex (75;76).…”
Section: Discussionmentioning
confidence: 99%